Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's solve for [tex]\( y \)[/tex] when [tex]\( x = 1 \)[/tex] using the given equation [tex]\( y = 2x + 4 \)[/tex].
1. We start with the given equation:
[tex]\[ y = 2x + 4 \][/tex]
2. Substitute [tex]\( x = 1 \)[/tex] into the equation:
[tex]\[ y = 2(1) + 4 \][/tex]
3. Now, perform the multiplication first:
[tex]\[ y = 2 \cdot 1 + 4 \][/tex]
[tex]\[ y = 2 + 4 \][/tex]
4. Finally, perform the addition:
[tex]\[ y = 6 \][/tex]
So, when [tex]\( x = 1 \)[/tex], the value of [tex]\( y \)[/tex] is [tex]\(\boxed{6}\)[/tex].
1. We start with the given equation:
[tex]\[ y = 2x + 4 \][/tex]
2. Substitute [tex]\( x = 1 \)[/tex] into the equation:
[tex]\[ y = 2(1) + 4 \][/tex]
3. Now, perform the multiplication first:
[tex]\[ y = 2 \cdot 1 + 4 \][/tex]
[tex]\[ y = 2 + 4 \][/tex]
4. Finally, perform the addition:
[tex]\[ y = 6 \][/tex]
So, when [tex]\( x = 1 \)[/tex], the value of [tex]\( y \)[/tex] is [tex]\(\boxed{6}\)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.